Polymorphisms in the CD14 and TLR4 genes independently predict CD4+ T-cell recovery in HIV-infected individuals on antiretroviral therapy. (10th September 2016) - Yong, Yean K.; Shankar, Esaki M.; Solomon, Ajantha; Spelman, Tim; Fairley, Christopher K.; Elliott, Julian H.; Hoy, Jennifer; Cameron, Paul U.; Kamarulzaman, Adeeba; Lewin, Sharon R.
Abstract : Background: Chronic HIV infection leads to marked depletion of CD4 + T cells in the gastrointestinal tract and increased microbial translocation measured by an increase in circulating lipopolysaccharide (LPS) levels. Here, we hypothesized that single-nucleotide polymorphisms (SNPs) in genes encoding the Toll-like receptor 4 (TLR4) and CD14, the principal receptors for LPS, were associated with CD4 + T-cell recovery postantiretroviral therapy (ART). Methods: Prospective study of predominantly white HIV-infected participants receiving suppressive ART for at least 12 months. We analysed the CD14 SNPs C-260T and the TLR4 SNPs A+896G, C+1196T. We also determined the levels of LPS and soluble CD14 in plasma samples collected pre-ART and post-ART initiation. CD4 + T-cell recovery was assessed by linear mixed models. Results: Following ART, individuals with a TT genotype compared with a CT or CC genotype for CD14 C-260T SNP showed higher levels of soluble CD14 ( P = 0.008 and 0.003, respectively). The CC genotype for the CD14 C-260T SNP, compared with CT or TT, and the TLR4 SNP (AC/GT), compared with the homozygous genotype (AA/CC), were both independently associated with enhanced long-term CD4 + T-cell recovery (>3 months; P < 0.001). Conclusion: Polymorphisms in CD14 and TLR4 are independently associated with long-term CD4 + T-cell recovery in HIV-infected individuals post-ART.